Small Cell Carcinoma of the Ovary, Hypercalcemic Type, in a 12-Month-Old Girl. (September 2021) - Atwi, Doaa; Quinton, Michael R; Kiser, Ryan M; Pokala, Hanumantha R; Rooms, Laura M; Yu, Zhongxin
Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) is a highly aggressive malignant tumor affecting predominantly young adults and adolescents with an average age of 23.9 at time of diagnosis. Up to two thirds of patients have paraneoplastic hypercalcemia. The molecular signature of these tumors is SMARCA4 mutations, with somatic and germline pathogenic variants previously described. We report a case of a previously healthy one-year-old girl who was noticed to have mild anemia and an abdominal mass during a well-child visit. Further laboratory testing revealed hypercalcemia. A computerized tomography scan showed a left-sided ovarian mass (9.3 x 7.3 x 7 cm). The resection specimen showed a large ovarian tumor with solid tan-yellow cut surfaces and small foci of necrosis. Microscopically, the tumor was composed of sheets of small, hyperchromatic epithelioid cells with focal rhabdoid large cell morphology. The tumor cells were strongly and diffusely positive for WT1 (N-terminal antibodies) with focal EMA and Pan-keratin positivity. Absent SMARCA4 (BRG1) protein expression by immunohistochemistry ultimately established the diagnosis of small cell carcinoma of the ovary, hypercalcemic type. To our knowledge, this is the youngest patient reported in the literature.